Workshop Perancangan dan Pelaksanaan Kegiatan Praktikum bagi Guru IPA di Kecamatan Nekamese - Kadek Ayu Astiti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This program is carried out in the form of a workshop for science teachers in partner schools to overcome the problems experienced by partners namely science teachers in SMP N 2 Nekamese and SMP N 3 Nekamese especially in terms of carrying out practical activities. Based on the problems encountered, several stages carried out in this activity include providing necessary science materials (physics, chemistry, biology) to improve understanding of the basic concepts of science for science teachers in partner schools, Theory and practice of using KIT media Science (mechanics, hydrostatic and heat, electricity and magnetism, optics), theory and practice of designing simple science practice activities, theory and practice of developing a simple science lab tool then carried out mentoring in carrying out practical exercises in the learning process and finally the evaluation phase. The results obtained after this activity was carried out were an increase in teachers 'knowledge of the science concept in an integrated manner, an increase in teachers' understanding and skills in using KIT physics, simple experimental design, and the design of a simple science lab tool. Participants were quite enthusiastic in participating in this activity as seen from the enthusiasm of coming to participate in activities and dynamic discussions. During the activity and further discussions, there were other problems that the partners had, namely the lack of teachers' ability to develop IT-based learning media. This can be a reference for future activities to realize a more varied and enjoyable learning process